EFFICIENCY OF NEW GENERATION SOLAR PHOTOELECTRIC BATTERIES - Buktukov, N.S.; Aitkulov, M. (Academic Journal of Physical and Chemical Sciences, 2018)
a solar photo-voltaic battery with a very high efficiency is Developed by dispersing and focusing solar radiation along wavelengths and installing an appropriate solar cell at each wavelength. This approach allows not only to increase efficiency, but also to increase battery life by eliminating infrared radiation on solar cells. In addition, the design allows cost-effective use of very expensive but highly efficient solar cells.